A 3D modeling strategy to predict efficiently cutting tool wear in longitudinal turning of AISI 1045 steel. Issue 1 (2021) - Courbon, C.; Fabre, D.; Methon, G.; Giovenco, A.; Cabanettes, F.; Rech, J.
Abstract: This work presents a numerical strategy to predict efficiently cutting tool wear in longitudinal turning. The full 3D cutting tool is discretized in elementary 2D sections. A FE based procedure is developed to compute in parallel the local contact pressure and sliding velocity along each section and update the tool profiles based on a tribologically identified wear equation. Results are merged to generate the 3D worn tool geometry while an iterative scheme is applied to achieve long simulated cutting time. Experimental cutting tests shown that a good agreement can be achieved in a reasonable computation time without any tuning parameter.